2016
DOI: 10.15587/1729-4061.2016.64294
|View full text |Cite
|
Sign up to set email alerts
|

Study of the protein-carbohydrate mix effect on the technological properties of short yeast-leavened dough

Abstract: *Кафедра технології в ресторанному господарстві та готельної і ресторанної справи Донецький національний університет економіки і торгівлі ім. Михайла Туган-Барановського вул. Островського, 16, м. Кривий Ріг, Україна, 50005

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The chemical composition of DPCS was also examined, it was found that the additive contains in its compound high-grade milk protein (over 10 %), pectin, easily digestible sugars, vitamins, macro-and microelements. It was also proven that the use of DPCS will not slow down technological processes that take place in the dough that is made on the pre-activated yeast medium [6].…”
Section: Results Of Research Into Effect Of Dpcs On the Structurally-mentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical composition of DPCS was also examined, it was found that the additive contains in its compound high-grade milk protein (over 10 %), pectin, easily digestible sugars, vitamins, macro-and microelements. It was also proven that the use of DPCS will not slow down technological processes that take place in the dough that is made on the pre-activated yeast medium [6].…”
Section: Results Of Research Into Effect Of Dpcs On the Structurally-mentioning
confidence: 99%
“…A promising direction in the development of technology of bread is the use of low-grade secondary raw materials of plant and animal origin, which are a source of enrichment of food and biological values of products [4] and contributes to the intensification of yeast fermentation [5,6].…”
Section: доказана перспективность использования сухого белково-углевоmentioning
confidence: 99%